Analysing depression using DASS-21 scale among diabetes in Malaysia - Mohd Ali, Salmiah; Musa, Nurul Ain; Musa, Ramli (2009)
Objectives: The study was aimed to verify the correlation and relationship that exist between depression and diabetes, through analysing demographic and disease related variables that may predict depression symptoms among diabetes patients. Methods: Diabetes patients (n=153) aged above 25 years old participated and were required to answer structured questionnaires about sociodemographic traits and the awareness of depression. DASS-21 questionnaires which consist of twenty-one questions examined on three scales;depression, anxiety and stress were used to evaluate depressive symptoms among the subjects. Pearson‘s correlation and multiple regression analysis were performed to assess the association of depressive symptoms with socio-demographic factors of age, gender, race, marital status, level of education and employment status. Habits and behaviours assessments containing six questions were also tested using the same method of analysis. Results: Socio-demographic traits showed significant correlation with the depression level among diabetes patients. Distribution of the patients according to gender showed not much difference in terms of percentage,whereby 51% were females and 49% were males. 6.53% of participants agreed to discuss their problems with depression with physicians. Conclusions: There was significant relationship between diabetes and depression. The underlying causes of depression might vary, thus, further studies should examine other factors that could contribute to depression.